Morphological Study and Conservation Status of JUNCAGENACEAE in Kurdistan Region, Iraq - Hama, Sakar Y.; Salih, Rubar Hussein M.; Ahmad, Saman A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
This study was conducted on the Juncaginaceae family in Iraq, which is a small monocot family of mostly coastal and wetland annual and perennial herbs of almost cosmopolitan distribution and represented by four genera, which are Triglochin, Lilaea, Maundia, and Tetroncium. There are approximately 25–35 species in the world. In Iraq, the family is represented by a single species, Triglochin palustris L. The T. palustris is characterized by perennial herbs, rhizome short, clothed with sheaths of old leaves. Stems are simple, erect or ascending, and 30–35 cm tall. Leaves are narrowly linear and semi-terete, inflorescence racemes, flowers are dark purple. Fruit is closely appressed to the scape, clavate, rachis, or ascending, with the ripe carpels separating from the base upwards. The species is widespread in Asia and extremely rare in Iraq, only found twice near the Persian frontier in the central sector of the lower thorn-cushion zone in the Rawanduz district (MRO), Haji Umran area, and Sakran Mountain. According to IUCN criteria, this family is critically endangered (CR) in Iraq. The process of identification and writing descriptions depended on the examination of all specimens and checking the various flora and guides. The main goal of this study is to rediscover and revise T. palustris and identify the conservation status of the family in Kurdistan, Iraq.